Dinamika Pendidikan Agama Islam Pada Era Khulafaur Rasyidin (632–661 M) - Komariah, Nining Syamsi; Ahmad Ubadi (Universitas Muhammadiyah Jember, 2025)
The era of the caliphs was an important period in the early development of Islamic civilization, including in the field of education. Although formal educational institutions such as madrasahs had not yet been formed, the intellectual, spiritual, and social foundations built during this period were very strong and influenced Islamic education in the following period. This study aims to explore more deeply the history of Islamic education, both before and during the reign of the caliphs. This research is based on qualitative literature studies, conducted through four main stages, namely: heuristics, criticism stage, interpretation stage aimed at interpreting verified historical data, and historiography stage, namely compiling the results of the analysis in the form of a systematic historical narrative. The results of the study, the development of Islamic education has progressed rapidly due to the social, political, and security situations marked by the establishment of Islamic educational institutions such as kuttab, mosques, and suffah.